6-minute walking test: a useful tool in the management of heart failure patients. (August 2019) - Giannitsi, Sophia; Bougiakli, Mara; Bechlioulis, Aris; Kotsia, Anna; Michalis, Lampros K.; Naka, Katerina K.
Reduced functional ability and exercise tolerance in patients with heart failure (HF) are associated with poor quality of life and a worse prognosis. The 6-minute walking test (6MWT) is a widely available and well-tolerated test for the assessment of the functional capacity of patients with HF. Although the cardiopulmonary exercise test (a maximal exercise test) remains the gold standard for the evaluation of exercise capacity in patients with HF, the 6MWT (submaximal exercise test) may provide reliable information about the patient's daily activity. The current review summarizes the value of 6MWT in patients with HF and identifies its usefulness and limitations in everyday clinical practice in populations of HF. We aimed to investigate potential associations of 6MWD with other measures of functional status and determinants of 6MWD in patients with HF as well as to review its prognostic role and changes to various interventions in these patients.